Room-temperature 1.2-J Fe2+:ZnSe laser. (January 2016) - Velikanov, S.D.; Zaretsky, N.A.; Zotov, E.A.; Kazantsev, S.Yu.; Kononov, I.G.; Korostelin, Yu.V.; Maneshkin, A.A.; Firsov, K.N.; Frolov, M.P.; Yutkin, I.M.
Abstract: The characteristics of a laser based on a single crystal pumped by an electric-discharge HF laser at room temperature are studied. The HF laser beam diameter on the crystal surface was . The achieved laser energy was with an efficiency of with respect to the pump energy.